TINGKAT KEPATUHAN DOKTER DALAM PENULISAN RESEP UNTUK PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM KOTA MATARAM - Annisaturrahmah Himawan (Nusadaya Journal of Multidiciplinary Studies, 2026)
Prescription writing is a crucial part of healthcare services and directly related to patient safety. Non-compliance with prescription writing can lead to medication errors, which impact the quality of care. This study aims to analyze the level of physician compliance in writing prescriptions for outpatients at Mataram City General Hospital. This study used a quantitative descriptive method with a cross-sectional approach. The study sample consisted of 200 prescriptions, which were analyzed using prescription completeness indicators based on pharmaceutical service standards. The results showed that physician compliance in writing prescriptions was quite good, with a compliance rate of 78%. However, incompleteness was still found in several components, such as the dosage, the doctor's signature, and the patient's identity. The conclusion of this study suggests that increased supervision and education are needed to improve physician compliance in writing prescriptions to ensure patient safety.